2018
DOI: 10.4155/fmc-2018-0511
|View full text |Cite
|
Sign up to set email alerts
|

NBGNU: a hypoxia-activated Tripartite combi-nitrosourea Prodrug Overcoming AGT-mediated Chemoresistance

Abstract: A hypoxia-activated combi-nitrosourea prodrug, N-(2-chloroethyl)-N -2-(2-(4-nitrobenzylcarbamate)-O 6 -benzyl-9-guanine)ethyl-N-nitrosourea (NBGNU), was synthesized and evaluated for its hypoxic selectivity and anticancer activity in vitro. Results: The prodrug was designed as a tripartite molecule consisting of a chloroethylnitrosourea pharmacophore to induce DNA interstrand crosslinks (ICLs) and an O 6 -benzylguanine analog moiety masked by a 4-nitrobenzylcarbamate group to induce hypoxia-activated inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Therefore, inhibiting AGT activity in tumor cells is of great significance for improving the chemotherapeutic effects of treatment. Over the past few decades, a series of AGT inhibitors have been synthesized for combination chemotherapy with alkylating agents [3,[16][17][18][19][20][21][22][23]. Among them, O 6 -benzylguanine (O 6 -BG) was the first AGT inhibitor to enter clinical trials with superior AGT inhibitory activity [3,15,24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibiting AGT activity in tumor cells is of great significance for improving the chemotherapeutic effects of treatment. Over the past few decades, a series of AGT inhibitors have been synthesized for combination chemotherapy with alkylating agents [3,[16][17][18][19][20][21][22][23]. Among them, O 6 -benzylguanine (O 6 -BG) was the first AGT inhibitor to enter clinical trials with superior AGT inhibitory activity [3,15,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effective anticancer therapeutic outcome of the O 6 -benzylguanine (O 6 -BG) was overshadowed by toxicity to normal cells and chemoresistance. Ge et al constructed N -(2-chloroethyl)- N ′-2-(2-(4-nitrobenzylcarbamate)-O 6 -benzyl-9-guanine)­ethyl- N -nitrosourea (NBGNU) by assembling a chloroethyl nitrosourea pharmacophore and an O 6 -benzylguanine analog moiety modified with a 4-nitrobenzylcarbamate group to inhibit O 6 -alkylguanine-DNA alkyltransferase . Under hypoxia, the reduction in product amounts and cell mortality rates stimulated by NBGNU were much higher than under normoxia.…”
Section: Utilizing Hypoxiamentioning
confidence: 99%
“…The most widely used nitrobenzyl trigger in prodrugs has been the 4-nitrosubstituted isomer, due partly to its overall higher one-electron reduction potentials (e.g., −356 mV for 4-nitroacetophenone (10) [23]. Ge et al [24] reported the 4-nitrobenzyl-triggered hypoxiaactivated nitrosourea prodrug NBGNU (11), which was designed to induce DNA interstrand crosslinks following reduction, by inhibiting O6-alkylguanine-DNA alkyltransferase, an enzyme which has the ability to suppress the chemotherapeutic effect of chloroethylnitrosoureas by removing drug-induced alkyl groups from the O6-site of guanine. In human glioma SF763 cells in culture, 11 was about 5-fold more potent under hypoxic compared to oxic cultures (IC 50 s 580 and 126 µM, respectively), with much higher levels of dG-dCd crosslinks in human brain glioma SF126 than cells treated with nimustine (12) under hypoxia (Figure 4).…”
Section: -Nitrobenzyl Triggersmentioning
confidence: 99%